Research Progress on Traditional Chinese Medicine Intervention for Diminished Ovarian Reserve - Yin, Wenxin; Li, Nan (Journal of Contemporary Medical Practice, 2025)
Diminished Ovarian Reserve (DOR) is a significant clinical issue that leads to decreased fertility in women and has been increasingly prevalent in recent years. While conventional Western medicine relies on ovulation induction and assisted reproductive technologies to improve pregnancy rates, these methods face challenges such as long treatment durations, significant side effects, and high costs. In contrast, Traditional Chinese Medicine (TCM) approaches to treating DOR, guided by theories such as "the kidney governing reproduction" and "the harmonization of Chong and Ren meridians," emphasize "syndrome differentiation and individualized treatment" and "holistic regulation." TCM demonstrates unique advantages in enhancing ovarian function, improving endocrine balance, and regulating emotions. This article systematically reviews the understanding of the etiology and pathogenesis of DOR in TCM, the characteristics of syndrome differentiation and typing, the mechanisms and therapeutic effects of herbal interventions, as well as the application progress of TCM-specific therapies such as acupuncture, moxibustion, medicinal fumigation, and foot baths. It also integrates modern medical research to validate their mechanisms of action and clinical value. TCM therapies not only provide safe and effective treatment options for patients with DOR but also offer theoretical foundations and practical directions for optimizing the management of women's reproductive health through the integration of traditional and Western medicine.